Role and mechanisms of exercise therapy in enhancing drug treatment for glioma: a review - Wu, Guanghui; Chen, Yisheng; Chen, Chong; Liu, Jianling; Wu, Qiaowu; Zhang, Yazhen; Chen, Runqiong; Xiao, Jianzhong; Su, Yusheng; Shi, Haojun; Yu, Chunsheng; Wang, Miao; et al. (Frontiers in Immunology, 2025)
Gliomas, particularly glioblastoma (GBM), are among the most aggressive and challenging brain tumors to treat. Although current therapies such as chemotherapy, radiotherapy, and targeted treatments have extended patient survival to some extent, their efficacy remains limited and is often accompanied by severe side effects. In recent years, exercise therapy has gained increasing attention as an adjunctive treatment in clinical and research settings. Exercise not only improves patients’ physical function and cognitive abilities but may also enhance the efficacy of conventional drug treatments by modulating the immune system, suppressing inflammatory responses, and improving blood-brain barrier permeability. This review summarizes the potential mechanisms of exercise in glioma treatment, including enhancing immune surveillance through activation of natural killer (NK) cells and T cells, and increasing drug penetration by improving blood-brain barrier function. Additionally, studies suggest that exercise can synergize with chemotherapy and immunotherapy, improving treatment outcomes while reducing drug-related side effects. Although the application of exercise therapy in glioma patients is still in the exploratory phase, existing evidence indicates its significant clinical value as an adjunctive approach, with the potential to become a new standard in glioma treatment in the future.